Unit 5 Notes
Unit 5 Notes
Unit 5 Notes
NOTES: CLASS-1
Periodic function:
A function 𝑓(𝑥) is said to be periodic if 𝑓(𝑥 + 𝑇) = 𝑓(𝑥) for all real 𝑥 and for some positive
number 𝑇. 𝑇 is known as the period of the 𝑓(𝑥).Fundamental period of 𝑓(𝑥) is the smallest period
of 𝑓.
Eg. 𝑐𝑜𝑠𝑥, 𝑠𝑖𝑛𝑥, 𝑠𝑒𝑐𝑥, 𝑐𝑜𝑠𝑒𝑐𝑥 are periodic functions with period 2𝜋.
Result1: If 𝑇 is the period of 𝑓(𝑥). Then 𝑛𝑇 is also period of 𝑓 for any integer 𝑛.
Result2:The function ℎ(𝑥) = 𝑎𝑓(𝑥) + 𝑏𝑔(𝑥) has period 𝑇 if 𝑓(𝑥)𝑎𝑛𝑑 𝑔(𝑥) have period 𝑇.
Result 3: If 𝑓(𝑥) is a periodic function of period 𝑇, then 𝑓(𝑎𝑥)𝑤𝑖𝑡ℎ 𝑎 ≠ 0, is a periodic function
𝑇
with period 𝑎.
Result 4: The period of a sum of a number of periodic function is the least common multiple of the
periods.
Result 5: A constant is periodic for any period 𝑇.
Trigonometric series is a fundamental series of the form 𝑓(𝑥) = 𝑎0 /2 + ∑∞
𝑛=1(𝑎𝑛 cos 𝑛𝑥 +
formulae gives the coefficient's 𝑎0 , 𝑎𝑛 , 𝑏𝑛 which are known as Fourier coefficients of 𝑓(𝑥).
Fourier Series
Fourier series of a periodic function 𝑓(𝑥) with period 2𝜋 is the trigonometric series (1) with the
Fourier coefficients 𝑎0 , 𝑎𝑛 , 𝑏𝑛 given by the Euler formulae (2),(3),(4).The individual terms in
Fourier series is known as harmonics.
Dirichlet conditions:
Let 𝑓(𝑥)be periodic function with period 2𝜋. Let 𝑓(𝑥) be a piecewise continuous, and bounded in
the interval (𝛼, 𝛼 + 2𝜋)with finite number of extrema. Then
1. at the point of continuity Fourier series of 𝑓(𝑥) (𝑅𝐻𝑆) 𝑐𝑜𝑛𝑣𝑒𝑟𝑔𝑒𝑠 𝑡𝑜 𝑓(𝑥)(𝐿𝐻𝑆).
2. At the point of discontinuity Fourier series of 𝑓(𝑥) converges to the arithmetic mean of left
and right hand limits of 𝑓(𝑥).
Problem 1. Obtain the Fourier series to represent 𝑒 −𝑎𝑥 from 𝑥 = −𝜋 to 𝑥 = 𝜋 . Hence derive the
𝜋
series for 𝑠𝑖𝑛ℎ𝜋
where,
1 𝜋
𝑎0 = ∫ 𝑓(𝑥)𝑑𝑥.
𝜋 −𝜋
1 𝜋
= 𝜋 ∫−𝜋 𝑒 −𝑎𝑥 𝑑𝑥
1 𝑒 −𝑎𝑥 𝜋
= 𝜋[ ]
−𝑎 −𝜋
−1
= 𝑎𝜋 [𝑒 −𝑎𝜋 − 𝑒 𝑎𝜋 ]
𝟐 𝒔𝒊𝒏 𝒉𝒂𝝅
𝒂𝟎 = 𝒂𝝅
1 𝜋
𝑎𝑛 = 𝜋 ∫−𝜋 𝑓(𝑥) 𝑐𝑜𝑠𝑛𝑥 𝑑𝑥
1 𝜋
= 𝜋 ∫−𝜋 𝑒 −𝑎𝑥 𝑐𝑜𝑠𝑛𝑥 𝑑𝑥
1 𝑒 −𝑎𝑥 𝜋
= 𝜋 [(−𝑎)2 +𝑛2 (−𝑎 𝑐𝑜𝑠𝑛𝑥 + 𝑛𝑠𝑖𝑛 𝑛𝑥)]
−𝜋
𝑒 𝑎𝑥
{𝑆𝑖𝑛𝑐𝑒, ∫ 𝑒 𝑎𝑥 𝑐𝑜𝑠𝑏𝑥 𝑑𝑥 = [𝑎2 +𝑏2 (𝑎 𝑐𝑜𝑠𝑏𝑥 + 𝑏𝑠𝑖𝑛 𝑏𝑥)]}
−𝑎 𝜋
= 𝜋(𝑎2 +𝑛2 ) [𝑒 −𝑎𝑥 𝑐𝑜𝑠𝑛𝑥]−𝜋
−𝑎 𝑐𝑜𝑠𝑛𝜋
= 𝜋(𝑎2 +𝑛2 )(𝑒 −𝑎𝜋 − 𝑒 𝑎𝜋 )
𝟐 𝐚 (−𝟏)𝒏 𝐬𝐢𝐧 𝒉 𝒂𝝅
𝒂𝒏 = 𝝅(𝒂𝟐 +𝒏𝟐 )
1𝜋
𝑏𝑛 = ∫ 𝑓(𝑥) 𝑠𝑖𝑛𝑛𝑥 𝑑𝑥
𝜋 −𝜋
1 𝜋
= 𝜋 ∫−𝜋 𝑒 −𝑎𝑥 𝑠𝑖𝑛𝑛𝑥 𝑑𝑥
1 𝑒 −𝑎𝑥 𝜋
= 𝜋 [(−𝑎)2 +𝑛2 (−𝑎 𝑠𝑖𝑛𝑛𝑥 − 𝑛𝑐𝑜𝑠 𝑛𝑥)]
−𝜋
𝑒 𝑎𝑥
𝑆𝑖𝑛𝑐𝑒 {∫ 𝑒 𝑎𝑥 𝑠𝑖𝑛𝑏𝑥 𝑑𝑥 = [𝑎2 +𝑏2 (𝑎 𝑠𝑖𝑛𝑏𝑥 − 𝑏𝑐𝑜𝑠 𝑏𝑥)]}
−𝑛 𝜋
= 𝜋(𝑎2 +𝑛2 ) [𝑒 −𝑎𝑥 𝑐𝑜𝑠𝑛𝑥]−𝜋
−𝑛 𝑐𝑜𝑠𝑛𝜋
= 𝜋(𝑎2 +𝑛2 )(𝑒 𝑎𝜋 − 𝑒 −𝑎𝜋 )
𝟐 𝐧 (−𝟏)𝒏 𝐬𝐢𝐧 𝒉 𝒂𝝅
𝒃𝒏 = 𝝅(𝒂𝟐 +𝒏𝟐 )
Therefore the required Fourier series is given by,
∞
𝑎0
𝑓(𝑥) = + ∑(𝑎𝑛 𝑐𝑜𝑠 𝑛𝑥 + 𝑏𝑛 sin 𝑛𝑥)
2
𝑛=1
1 𝟐 𝐬𝐢𝐧 𝒉𝒂𝝅 𝟐 𝐚 (−𝟏)𝒏 𝐬𝐢𝐧 𝒉 𝒂𝝅 𝟐 𝐧 (−𝟏)𝒏 𝐬𝐢𝐧 𝒉 𝒂𝝅
𝑒 −𝑎𝑥 = +∑∞
𝑛=1 ( 𝑐𝑜𝑠 𝑛𝑥 + sin 𝑛𝑥)
2 𝒂𝝅 𝝅(𝒂𝟐 +𝒏𝟐 ) 𝝅(𝒂𝟐 +𝒏𝟐 )
Deduction :
To deduce the series we shall put 𝑎 = 1, 𝑥 = 0 in the above equation :
sin ℎ𝜋 2(−1)𝑛
𝑒 0= {1 + ∑∞
𝑛=1 ((1+𝑛2 ) 𝑐𝑜𝑠 𝑛(0)) }
𝜋
sin ℎ𝜋 2(−1)𝑛
⟹1 = {1 + ∑∞
𝑛=1 ((1+𝑛2 )) }
𝜋
𝜋 −1 1 −1 1
⟹ 𝑠𝑖𝑛ℎ𝜋 = 1+2(1+12 + 1+22 + 1+32 + 1+42 + ⋯ )
𝜋 1 1 1
⟹ 𝑠𝑖𝑛ℎ𝜋 = 1 − 1 + 2 (1+22 − 1+32 + 1+42 − ⋯ )
𝝅 𝟏 𝟏 𝟏
⟹ 𝒔𝒊𝒏𝒉𝝅 = 2(𝟏+𝟐𝟐 − 𝟏+𝟑𝟐 + 𝟏+𝟒𝟐 − ⋯ … … … . . )
--------------------------------------------------------------------------------------------------------------------
REFERENCES:
1. Higher Engineering Mathematics-B.S. Grewal
2. Higher Engineering Mathematics-B.V. Ramana
*************************************************************
NOTES: CLASS-2
Fourier Series of Even and Odd functions
A function 𝑓(𝑥) is said to be even if 𝑓(−𝑥) = 𝑓(𝑥) ∀𝑥.and odd if 𝑓(−𝑥) = −𝑓(𝑥) ∀𝑥.
Fourier series of an even function 𝑓(𝑥)𝑖𝑛 (−𝜋, 𝜋) contains only cosine terms and is known as
Fourier cosine series given by
∞
Fourier series of an odd function 𝑓(𝑥)𝑖𝑛 (−𝜋, 𝜋) contains only sine terms and is known as Fourier
sine series given by
1 𝜋 2 𝜋
𝑓(𝑥) = ∑∞
𝑛=1(𝑏𝑛 𝑠𝑖𝑛𝑛𝑥) Where 𝑏𝑛 = 𝜋 ∫−𝜋 𝑓(𝑥)𝑠𝑖𝑛𝑛𝑥𝑑𝑥 = 𝜋 ∫0 𝑓(𝑥)𝑠𝑖𝑛𝑛𝑥𝑑𝑥
1 𝑐+2𝐿 𝑛𝜋𝑥
𝑎𝑛 = ∫ 𝑓(𝑥)cos( )𝑑𝑥
𝐿 𝑐 𝐿
1 𝑐+2𝐿 𝑛𝜋𝑥
𝑏𝑛 = ∫ 𝑓(𝑥) sin ( ) 𝑑𝑥.
𝐿 𝑐 𝐿
Fourier series for even and odd functions defined in (−𝑳, 𝑳)
Fourier series of an even function 𝑓(𝑥)𝑖𝑛 (−𝐿, 𝐿) contains only cosine terms and is known as
Fourier cosine series given by
∞
𝑛𝜋𝑥
𝑓(𝑥) = 𝑎0 /2 + ∑ (𝑎𝑛 𝑐𝑜𝑠 )
𝐿
𝑛=1
1 𝐿 2 𝐿
Where 𝑎0 = 𝐿 ∫−𝐿 𝑓(𝑥)𝑑𝑥 = 𝐿 ∫0 𝑓(𝑥)𝑑𝑥
1 𝐿 𝑛𝜋𝑥 2 𝐿 𝑛𝜋𝑥
And 𝑎𝑛 = 𝐿 ∫−𝐿 𝑓(𝑥)𝑐𝑜𝑠 𝑑𝑥 = 𝐿 ∫0 𝑓(𝑥)𝑐𝑜𝑠 𝑑𝑥
𝐿 𝐿
Fourier series of an odd function 𝑓(𝑥)𝑖𝑛 (−𝐿, 𝐿) contains only sine terms and is known as Fourier
sine series given by
∞
𝑛𝜋𝑥
𝑓(𝑥) = ∑ (𝑏𝑛 𝑠𝑖𝑛 )
𝐿
𝑛=1
1 𝐿 𝑛𝜋𝑥 2 𝐿 𝑛𝜋𝑥
Where 𝑏𝑛 = 𝐿 ∫−𝐿 𝑓(𝑥)𝑠𝑖𝑛 𝑑𝑥 = 𝐿 ∫0 𝑓(𝑥)𝑠𝑖𝑛 𝑑𝑥
𝐿 𝐿
Problem 1. Find the Fourier Series expansion of 𝑓(𝑥) = 𝑥(1 − 𝑥)(2 − 𝑥) in (0,2). Deduce the
1 1 1 1
sum of the series 13 − 33 + 53 − 73 +…..
where
2
𝑎0 = ∫ 𝑓(𝑥)𝑑𝑥.
0
2
= ∫0 2𝑥 − 3𝑥 2 + 𝑥 3 𝑑𝑥.
2
𝑥2 𝑥3 𝑥4
= [2 2
−3 3
+ 4
]
0
16
=4−8+ 4
⟹ 𝑎0 = 0
2
𝑎𝑛 = ∫ 𝑓(𝑥)𝑐𝑜𝑠𝑛𝜋𝑥𝑑𝑥
0
2
= ∫ (2𝑥 − 3𝑥 2 + 𝑥 3 )𝑐𝑜𝑠𝑛𝜋𝑥𝑑𝑥
0
sin(𝑛𝜋𝑥) −𝑐𝑜𝑠(𝑛𝜋𝑥) −𝑠𝑖𝑛(𝑛𝜋𝑥)
= [(2𝑥 − 3𝑥 2 + 𝑥 3 ) ( ) − (2 − 6𝑥 + 3𝑥 2 ) ( (𝑛𝜋)2
) + (−6 + 6𝑥) ( (𝑛𝜋)3
) −
𝑛𝜋
𝑐𝑜𝑠(𝑛𝜋𝑥) 2
(6) ( (𝑛𝜋)4
)]
0
−𝑐𝑜𝑠(𝑛𝜋𝑥) 𝑎𝑜𝑠(𝑛𝜋𝑥) 2
= [(2 − 6𝑥 + 3𝑥 2 ) ( (𝑛𝜋)2
) + (−6) ( (𝑛𝜋)4
)]
0
−𝑐𝑜𝑠(2𝑛𝜋) −1 𝑐𝑜𝑠(2𝑛𝜋) 1
= [(2) ( (𝑛𝜋)2
) − (2) ((𝑛𝜋)2 )] + [(−6) ( (𝑛𝜋)4
) − (−6) ((𝑛𝜋)4 )]
⟹ 𝑎𝑛 = 0
2
𝑏𝑛 = ∫ 𝑓(𝑥)𝑠𝑖𝑛𝑛𝜋𝑥𝑑𝑥
0
2
= ∫0 (2𝑥 − 3𝑥 2 + 𝑥 3 ) 𝑠𝑖𝑛𝑛𝜋𝑥𝑑𝑥
−𝑠𝑖𝑛(𝑛𝜋𝑥) 𝑐𝑜𝑠(𝑛𝜋𝑥)
= [(2𝑥 − 3𝑥 2 + 𝑥 3 )(− cos 𝑛𝜋𝑥 ) − (2 − 6𝑥 + 3𝑥 2 ) ( (𝑛𝜋)2
) + (−6 + 6𝑥) ( (𝑛𝜋)3
) −
𝑠𝑖𝑛(𝑛𝜋𝑥) 2
(6) ( (𝑛𝜋)4
)]
0
𝑐𝑜𝑠(𝑛𝜋𝑥) 2
= [(2𝑥 − 3𝑥 2 + 𝑥 3 )(− cos 𝑛𝜋𝑥 ) + (−6 + 6𝑥) ( (𝑛𝜋)3
)]
0
𝑐𝑜𝑠(2𝑛𝜋) 1
= [(0)(−𝑐𝑜𝑠2𝑛𝜋) − (0)(−1)] + [(6) ( (𝑛𝜋)3
) − (−6) ((𝑛𝜋)3 )]
12
⟹ 𝑏𝑛 = 𝑛3 𝜋3
Deduction :
1
To deduce the series we shall put 𝑥 = in the above equation,
2
∞
1 12 1
𝑓 ( ) = ∑ [ 3 3 sin 𝑛𝜋 ( )]
2 𝑛 𝜋 2
𝑛=1
∞
1 1 2 1 3 12 1 𝑛𝜋
⟹ 2 ( ) − 3 ( ) + ( ) = 3 ∑ [ 3 𝑠𝑖𝑛 ( )]
2 2 2 𝜋 𝑛 2
𝑛=1
1 1 1 1 𝜋3
⟹ 13 − 33 +53 − 73 + ⋯ … … … … … … . = 32
REFERENCES:
1. Higher Engineering Mathematics-B.S. Grewal
2. Higher Engineering Mathematics-B.V. Ramana
*************************************************************
NOTES: CLASS-3
1. Find the Fourier Series of 𝑓(𝑥) = 𝑥 + 𝑥 2 in (−𝜋, 𝜋 ).
1 𝜋2
Hence deduce that ∑∞
𝑛=1 𝑛2 = 6
where
1 𝜋
𝑎0 = ∫ 𝑓(𝑥)𝑑𝑥.
𝜋 −𝜋
1 𝜋
= 𝜋 ∫−𝜋 𝑥 + 𝑥 2 𝑑𝑥
𝜋
1 𝑥2 𝑥3
= 𝜋[2 + ]
3 −𝜋
1 𝜋2 𝜋3 𝜋2 𝜋3
= 𝜋[2 + − + ]
3 2 3
𝟐𝝅𝟐
⟹ 𝒂𝟎 = 𝟑
1 𝜋
𝑎𝑛 = ∫ 𝑓(𝑥) 𝑐𝑜𝑠𝑛𝑥 𝑑𝑥
𝜋 −𝜋
1 𝜋
= 𝜋 ∫−𝜋(𝑥 + 𝑥 2 )𝑐𝑜𝑠𝑛𝑥 𝑑𝑥
1 sin 𝑛𝑥 cos 𝑛𝑥 sin 𝑛𝑥 𝜋
= 𝜋 [(𝑥 + 𝑥 2 ) ( ) − (1 + 2𝑥) (− ) + 2 (− )]
𝑛 𝑛2 𝑛3 −𝜋
1 cos 𝑛𝑥 𝜋
= 𝜋 [(1 + 2𝑥) ( )]
𝑛2 −𝜋
1
= 𝜋𝑛2 [(1 + 2𝜋) cos 𝑛𝜋 − (1 + 2(−𝜋)𝑐𝑜𝑠𝑛(−𝜋)]
1
= 𝜋𝑛2 (4𝜋)cos 𝑛𝜋
𝟒
⟹ 𝒂𝒏 = (−𝟏)𝒏
𝒏𝟐
1 𝜋
𝑏𝑛 = 𝜋 ∫−𝜋 𝑓(𝑥) 𝑠𝑖𝑛𝑛𝑥 𝑑𝑥
1 𝜋
= 𝜋 ∫−𝜋(𝑥 + 𝑥 2 )𝑠𝑖𝑛𝑛𝑥 𝑑𝑥
1 cos 𝑛𝑥 sin 𝑛𝑥 cos 𝑛𝑥 𝜋
= 𝜋 [(𝑥 + 𝑥 2 ) (− ) − (1 + 2𝑥) (− ) + 2( )]
𝑛 𝑛2 𝑛3 −𝜋
1 cos 𝑛𝑥 cos 𝑛𝑥 𝜋
= 𝜋 [(𝑥 + 𝑥 2 ) (− ) + 2( )]
𝑛 𝑛3 −𝜋
1 cos 𝑛𝜋 cos 𝑛𝜋 cos 𝑛(−𝜋) cos 𝑛(−𝜋)
= 𝜋𝑛2 [(𝜋 + 𝜋 2 ) (− )+ 2( ) − (−𝜋 + (−𝜋)2 ) (− ) + 2( )]
𝑛 𝑛3 𝑛 𝑛3
−1
= (2𝜋) cos 𝑛𝜋
𝜋𝑛
−2
= (−1)𝑛
𝑛
𝟐
⟹ 𝒃𝒏 = (−𝟏)𝒏+𝟏
𝒏
𝝅𝟐 𝟒 𝟐
⟹ 𝒙 + 𝒙𝟐 = + ∑∞ 𝒏
𝒏=𝟏 (𝒏𝟐 (−𝟏) 𝒄𝒐𝒔 𝒏𝒙 + 𝒏 (−𝟏)
𝒏+𝟏
𝐬𝐢𝐧 𝒏𝒙) … . . … … … (𝟏)
𝟑
Deduction :
To deduce the series we shall put 𝑥 = −𝜋 in the above equation.
Here 𝑓(𝑥) = 𝑥 + 𝑥 2 is valid for all values of 𝑥 between – 𝜋 and 𝜋 but not at the end points since
the given interval is open. Therefore, 𝑥 = −𝜋 is a point of discontinuity and hence,
1
𝑓(−𝜋) = 2 [𝑓(−𝜋 − 0) + 𝑓(−𝜋 + 0)]
1
= 2 [𝑓(𝜋 − 0) + 𝑓(−𝜋 + 0)] (since 𝑓(𝑥) is periodic with 2𝜋)
1
= 2 [𝜋 + 𝜋 2 + (−𝜋) + (−𝜋)2 ]
⟹ 𝒇(−𝝅) = 𝝅𝟐 … … … … … … … (𝟐)
Substituting the value of 𝑓(−𝜋) from (2) and putting 𝑥 = 𝜋 in (1) we obtain,
𝜋2 1 1 1 1 1
𝜋2= + 4 [12 + 22 + 32 + 42 + 52 + ⋯ ]
3
Simplifying, we get,
𝝅𝟐 𝟏 𝟏 𝟏 𝟏 𝟏
= 𝟏𝟐 + 𝟐𝟐 + 𝟑𝟐 + 𝟒𝟐 + 𝟓𝟐 + ⋯……………..
𝟔
REFERENCES:
1. Higher Engineering Mathematics-B.S. Grewal
2. Higher Engineering Mathematics-B.V. Ramana
*************************************************************
NOTES: CLASS-4
−𝜋 , −𝜋 <𝑥 <0
2. Obtain the Fourier series for 𝑓(𝑥) = { }
𝑥 , 0<𝑥<𝜋
𝜋2 1 1 1
Hence deduce that = + 32 + 52 + ⋯
8 12
where
1 𝜋
𝑎0 = ∫ 𝑓(𝑥)𝑑𝑥.
𝜋 −𝜋
1 0 𝜋
= 𝜋 [∫−𝜋 −𝜋 𝑑𝑥 + ∫0 𝑥 𝑑𝑥]
𝜋
1 𝑥2
= 𝜋 {[−𝜋(𝑥)]0−𝜋 + [ 2 ] }
0
1 𝜋2
= 𝜋 [−𝜋 2 + ]
2
𝝅
⟹ 𝒂𝟎 = − 𝟐
1 𝜋
𝑎𝑛 = ∫ 𝑓(𝑥) 𝑐𝑜𝑠𝑛𝑥 𝑑𝑥
𝜋 −𝜋
1 0 𝜋 1 0 𝜋
= 𝜋 [∫−𝜋 𝑓(𝑥)𝑐𝑜𝑠𝑛𝑥 𝑑𝑥 + ∫0 𝑓(𝑥)𝑐𝑜𝑠𝑛𝑥 𝑑𝑥] + 𝜋 [∫−𝜋 −𝜋 𝑐𝑜𝑠𝑛𝑥 𝑑𝑥 + ∫0 𝑥 𝑐𝑜𝑠𝑛𝑥 𝑑𝑥 ]
1 𝜋
𝑏𝑛 = ∫ 𝑓(𝑥) 𝑠𝑖𝑛𝑛𝑥 𝑑𝑥
𝜋 −𝜋
1 0 𝜋 1 0 𝜋
= 𝜋 [∫−𝜋 𝑓(𝑥)𝑠𝑖𝑛𝑛𝑥 𝑑𝑥 + ∫0 𝑓(𝑥)𝑠𝑖𝑛𝑛𝑥 𝑑𝑥] + 𝜋 [∫−𝜋 −𝜋 𝑠𝑖𝑛𝑛𝑥 𝑑𝑥 + ∫0 𝑥 𝑠𝑖𝑛𝑛𝑛𝑥 𝑑𝑥 ]
0
1 − cos 𝑛𝑥 −cos 𝑛𝑥 𝜋 sin 𝑛𝑥 𝜋
= [−𝜋 [ ] + [𝑥. ] − [− ] ]
𝜋 𝑛 −𝜋 𝑛 0 𝑛2 0
1 0 𝜋
= 𝜋(𝑛) {[ 𝜋𝑐𝑜𝑠𝑛𝑥]−𝜋 − [ 𝑥𝑐𝑜𝑠𝑛𝑥]0 }
1
= 𝜋𝑛2 [ 𝜋𝑐𝑜𝑠𝑛(0) − 𝜋𝑐𝑜𝑠𝑛𝜋 − [𝜋𝑐𝑜𝑠𝑛(𝜋) − 0]]
1
⟹ 𝑏𝑛 = 𝑛 [1 − 2 (−1)𝑛 ]
−𝜋 1 1
⟹ 𝑓(𝑥) = + ∑∞ 𝑛 𝑛
𝑛=1 {𝜋𝑛2 [ (−1) − 1]𝑐𝑜𝑠 𝑛𝑥 + 𝑛 [1 − 2 (−1) ] sin 𝑛𝑥}
4
Deduction :
To deduce the series we shall put 𝑥 = 0 in the above equation.
π 1
𝑓(0) = − 4 + ∑∞ n
n=1 {πn2 [ (−1) − 1]cos n(0)}
Therefore,
∞
−𝜋 − 𝜋 −1 1
= + ∑ ( 2 [1 − (−1)𝑛 ])
2 4 𝜋 𝑛
𝑛=1
𝜋 𝜋 1 2 2 2
⟹ = + 𝜋 (12 + 32 + 52 + ⋯ )
2 4
1 1 1 𝜋2
⟹ + + + ⋯ … … … … … … … … . . . =
12 32 52 8
--------------------------------------------------------------------------------------------------------------------
2. Express 𝑓(𝑥) = (𝜋 − 𝑥)2 as a Fourier Series of period 2𝜋 in the interval 0 < 𝑥 < 2𝜋 and
1 1
hence deduce the sum of the series 1 + 22 + 32 + ⋯
where
1 2𝜋
𝑎0 = ∫ 𝑓(𝑥)𝑑𝑥.
𝜋 0
1 2𝜋
= 𝜋 ∫0 (𝜋 − 𝑥)2 𝑑𝑥
2𝜋
1 (𝜋−𝑥)3
= 𝜋 [ 3(−1) ]
0
−1 −𝜋3 𝜋3
= [ − ]
𝜋 3 3
𝟐𝝅𝟐
⟹ 𝑎0 = 𝟑
1 2𝜋
𝑎𝑛 = 𝜋 ∫0 𝑓(𝑥) 𝑐𝑜𝑠𝑛𝑥 𝑑𝑥
1 2𝜋
= 𝜋 ∫0 (𝜋 − 𝑥)2 𝑐𝑜𝑠𝑛𝑥 𝑑𝑥
1 sin 𝑛𝑥 cos 𝑛𝑥 sin 𝑛𝑥 2𝜋
= 𝜋 [(𝜋 − 𝑥)2 ) ( ) − 2(𝜋 − 𝑥)(−1) (− ) + 2(−1) (− )]
𝑛 𝑛2 𝑛3 0
1 cos 𝑛𝑥 2𝜋
= 𝑓 [2(𝜋 − 𝑥) (− )]
𝑛2 0
1
= 𝜋𝑛2 [+2𝜋(𝑐𝑜𝑠2𝑛𝜋) + 2𝜋𝑐𝑜𝑠𝑛(0)]
1
= (4 𝜋 )
𝜋𝑛2
𝟒
⟹ 𝑎𝑛 = 𝒏𝟐
1 2𝜋
𝑏𝑛 = ∫ 𝑓(𝑥) 𝑠𝑖𝑛𝑛𝑥 𝑑𝑥
𝜋 0
1 2𝜋
= 𝜋 ∫0 (𝜋 − 𝑥)2 𝑠𝑖𝑛𝑛𝑥 𝑑𝑥
−cos 𝑛𝑥 sin 𝑛𝑥 cos 𝑛𝑥 2𝜋
1 (𝜋 − 𝑥)2 ) ( ) − 2(𝜋 − 𝑥)(−1) (− ) + 2(+1) ( )
= 𝜋[ 𝑛 𝑛2 𝑛3 ]
0
1 −cos 𝑛𝑥 2 2𝜋
= 𝜋 [(𝜋 − 𝑥)2 ) ( ) + 𝑛3 (𝑐𝑜𝑠𝑛𝑥)]
𝑛 0
⟹ 𝑏𝑛 =0
Deduction :
To deduce the series we shall put 𝑥 = 0 in the above the series
π2 4
𝑓(0) = + ∑∞
n=1 (n2 cos n(0))
3
1 1 1 𝜋2
⟹ + + + ⋯ … … … … … … … … =
12 22 32 6
REFERENCES:
1. Higher Engineering Mathematics-B.S. Grewal
2. Higher Engineering Mathematics-B.V. Ramana
*************************************************************
NOTES: CLASS-5
Half Range Fourier series of f(x) in(0,𝞹)
Cosine series
∞
𝑎0
𝑓(𝑥) = + ∑ 𝑎𝑛 𝑐𝑜𝑠 𝑛𝑥
2
𝑛=1
Fourier Coefficients:
𝟐 𝝅
𝑎0 = ∫ 𝒇(𝒙)𝒅𝒙.
𝝅 𝟎
𝟐 𝝅
𝑎𝑛 = ∫ 𝒇(𝒙) 𝒄𝒐𝒔𝒏𝒙 𝒅𝒙
𝝅 𝟎
Sine Series
∞
𝑓(𝑥) = ∑ 𝑏𝑛 sin 𝑛𝑥
𝑛=1
Fourier Coefficients:
𝟐 𝝅
𝑏𝑛 = ∫ 𝒇(𝒙) 𝒔𝒊𝒏𝒏𝒙 𝒅𝒙
𝝅 𝟎
Half Range Fourier series of f(x) in (0,l):
Cosine series
∞
𝑎0 𝑛𝜋𝑥
𝑓(𝑥) = + ∑ 𝑎𝑛 𝑐𝑜𝑠
2 𝑙
𝑛=1
Fourier Coefficients:
𝟐 𝒍
𝑎0 = ∫ 𝒇(𝒙)𝒅𝒙.
𝒍 𝟎
𝟐 𝒍 𝑛𝜋𝑥
𝑎𝑛 = ∫ 𝒇(𝒙) 𝒄𝒐𝒔 𝒅𝒙
𝒍 𝟎 𝑙
Sine Series
∞
𝑛𝜋𝑥
𝑓(𝑥) = ∑ 𝑏𝑛 sin
𝑙
𝑛=1
Fourier Coefficients:
𝟐 𝒍 𝒏𝝅𝒙
𝑏𝑛 = ∫ 𝒇(𝒙) 𝒔𝒊𝒏 𝒅𝒙
𝒍 𝟎 𝒍
Problem 1 . Obtain the Fourier expansion of the function 𝑓(𝑥) = 𝑥𝑠𝑖𝑛𝑥, as a cosine series in
(0, 𝜋).
Solution : The Fourier cosine series is given by,
𝑎0
𝑓(𝑥) = + ∑∞
𝑛=1 𝑎𝑛 𝑐𝑜𝑠𝑛𝑥
2
where
𝜋
2
𝑎0 = ∫ 𝑥𝑠𝑖𝑛𝑥𝑑𝑥
𝜋
0
2
= 𝜋 [𝑥(−𝑐𝑜𝑠𝑥) − (1)(−𝑠𝑖𝑛𝑥)]𝜋0
−2
= {𝜋 cos 𝜋 − 0}
𝜋
⟹ 𝑎0 = 2
𝜋
2
𝑎𝑛 = ∫ 𝑥𝑠𝑖𝑛𝑥𝑐𝑜𝑠𝑛𝑥𝑑𝑥
𝜋
0
1 𝜋
= ∫0 𝑥[𝑠𝑖𝑛(𝑛 + 1)𝑥 − sin(𝑛 − 1)]𝑑𝑥
𝜋
𝜋
1 cos(𝑛+1)𝑥 cos(𝑛−1)𝑥 sin(𝑛+1)𝑥 sin(𝑛−1)𝑥
= 𝜋 𝑥. [− + − (1). [− + ]]
𝑛+1 𝑛−1 𝑛+1 𝑛−1
0
1 𝜋(−1)𝑛+1 (−1)𝑛−1
= 𝜋 [− +𝜋 ]
𝑛+1 𝑛−1
𝜋(−1)𝑛 1 1
= [𝑛+1 − 𝑛−1]
𝜋
−2
= (−1)𝑛 [𝑛2 −1]
𝟐(−𝟏)𝒏+𝟏
⟹ 𝑎𝑛 = where 𝑛 ≠ 1
𝒏𝟐 −𝟏
When 𝒏 = 𝟏,
𝜋
2
𝑎1 = ∫ 𝑥𝑠𝑖𝑛𝑥𝑐𝑜𝑠𝑥𝑑𝑥
𝜋
0
1 𝜋
= 𝜋 ∫0 𝑥𝑠𝑖𝑛2𝑥𝑑𝑥
1 𝑥(−𝑐𝑜𝑠2𝑥) (1)(−𝑠𝑖𝑛2𝑥) 𝜋
= 𝜋[ − ]
2 4 0
1[−𝜋]
= 2𝜋
𝟏
⟹ 𝑎𝑛 = 𝟐
--------------------------------------------------------------------------------------------------------------------
Problem 2. Find the Fourier half range a) Cosine series b) Sine series of
𝒙, 𝟎 < 𝒙 < 𝟏
𝐟(𝒙) = {
𝟐 − 𝒙, 1 < 𝑥 < 𝟐
Solution : The Half Range Fourier Cosine series is given by,
∞
𝑎0 𝑛𝜋𝑥
𝑓(𝑥) = + ∑ 𝑎𝑛 𝑐𝑜𝑠
2 𝑙
𝑛=1
where
2
2
𝑎0 = ∫ 𝑓(𝑥)𝑑𝑥
2
0
1 2
= ∫0 𝑥 𝑑𝑥 + ∫1 (2 − 𝑥)dx
1 2
𝑥2 𝑥2
= [ 2 ] + [2𝑥 − ]
0 2 1
=1
2 𝑙 𝑛𝜋𝑥
𝑎𝑛 = ∫ 𝑓(𝑥) 𝑐𝑜𝑠 𝑑𝑥
𝑙 0 𝑙
2
2 𝑛𝜋𝑥
= ∫ 𝑓(𝑥)𝑐𝑜𝑠 𝑑𝑥
2 2
0
1 𝑛𝜋𝑥 2 𝑛𝜋𝑥
= ∫0 𝑥 𝑐𝑜𝑠 𝑑𝑥 + ∫1 (2 − 𝑥)𝑐𝑜𝑠 𝑑𝑥
2 2
𝑛𝜋𝑥 1 𝑛𝜋𝑥 1 𝑛𝜋𝑥 2 𝑛𝜋𝑥 2
sin cos sin cos
2 2 2 2
= [𝑥. 𝑛𝜋 ] − [− 𝑛2 𝜋2
] + [(2 − 𝑥). 𝑛𝜋 ] −[ 𝑛2 𝜋2
]
2 0 4 2 1 4
0 1
2 𝑛𝜋 4 𝑛𝜋 2 𝑛𝜋 4 𝑛𝜋
= 𝑛𝜋 sin( 2 )+𝑛2 𝜋2 [𝑐𝑜𝑠 ( 2 ) − 1] − 𝑛𝜋 sin( 2 ) − 𝑛2 𝜋2 [𝑐𝑜𝑠𝑛𝜋 − 𝑐𝑜𝑠 ( 2 )]
8 𝑛𝜋 4
= 𝑛2 𝜋2 𝑐𝑜𝑠 ( 2 ) − 𝑛2 𝜋2 [1 + (−1)𝑛 ]
𝑛𝜋𝑥
b) The Half range Fourier Sine series is given by, 𝑓(𝑥) = ∑∞
𝑛=1 𝑏𝑛 sin 𝑙
𝟐 𝒍 𝑛𝜋𝑥
𝑤ℎ𝑒𝑟𝑒 𝑏𝑛 = ∫ 𝑓(𝑥) 𝑠𝑖𝑛 𝑑𝑥
𝒍 𝟎 𝑙
2 2 𝑛𝜋𝑥
= 2 ∫0 𝑓(𝑥)𝑠𝑖𝑛 𝑑𝑥
2
1 𝑛𝜋𝑥 2 𝑛𝜋𝑥
= ∫0 𝑥 𝑠𝑖𝑛 𝑑𝑥 + ∫1 (2 − 𝑥)𝑠𝑖𝑛 𝑑𝑥
2 2
𝑛𝜋𝑥 1 𝑛𝜋𝑥 1 𝑛𝜋𝑥 2 𝑛𝜋𝑥 2
−cos s 𝑖𝑛 −𝑐𝑜𝑠 sin
2 2 2 2
=[𝑥. 𝑛𝜋 ] − [− 𝑛2 𝜋2
] + [(2 − 𝑥). 𝑛𝜋 ] −[ 𝑛2 𝜋2
]
2 0 4 2 1 4
0 1
−2 𝑛𝜋 4 𝑛𝜋 2 𝑛𝜋 4 𝑛𝜋
= cos( )+ [𝑠𝑖𝑛 ( )] + cos( ) − [0 − 𝑠𝑖𝑛 ( )]
𝑛𝜋 2 𝑛2 𝜋 2 2 𝑛𝜋 2 𝑛2 𝜋 2 2
8 𝑛𝜋
= 𝑛2 𝜋2 sin( 2 )
Therefore,
𝑎0 𝑛𝜋𝑥
i. Half range Cosine series: 𝑓(𝑥) = + ∑∞
𝑛=1 𝑎𝑛 𝑐𝑜𝑠
2 2
1 8 𝑛𝜋 4 𝑛𝜋𝑥
⟹ 𝑓(𝑥) = 2 + ∑∞ 𝑛
𝑛=1 𝑛2 𝜋 2 𝑐𝑜𝑠 ( 2 ) − 𝑛2 𝜋 2 [1 + (−1) ]𝑐𝑜𝑠 2
𝑛𝜋𝑥
ii. Half range Sine series :𝑓(𝑥) = ∑∞
𝑛=1 𝑏𝑛 sin 𝑙
∞
8 𝑛𝜋 𝑛𝜋𝑥
⟹ 𝑓(𝑥) = ∑ sin ( ) sin
𝑛2 𝜋 2 2 2
𝑛=1
Problem 3. By using the sine series for 𝑓(𝑥) = 1 in 0 < 𝑥 < 𝜋. Hence show that,
1 1 1 𝜋2
+ 32 + 52 + ⋯ = .
12 8
𝑓(𝑥) = ∑ 𝑏𝑛 sin 𝑛𝑥
𝑛=1
2 𝜋
𝑤ℎ𝑒𝑟𝑒 𝑏𝑛 = ∫ 𝑓(𝑥) 𝑠𝑖𝑛𝑛𝑥 𝑑𝑥
𝜋 0
2 𝜋
⟹ 𝑏𝑛 = 𝜋 ∫0 (1) 𝑠𝑖𝑛𝑛𝑥 𝑑𝑥
2 −𝑐𝑜𝑠𝑛𝑥 𝜋 −2
= 𝜋[ ] = 𝑛𝜋 [𝑐𝑜𝑠𝑛𝜋 − 1]
𝑛 0
−2
= 𝑛𝜋 [(−1)𝑛 − 1]
2
= 𝑛𝜋 [1 − (−1)𝑛 ]
4 𝑠𝑖𝑛3𝑥 𝑠𝑖𝑛5𝑥
⟹1= (𝑠𝑖𝑛𝑥 + + + ⋯.)
𝜋 3 5
Deduction :
Consider the Parseval’s identity for odd functions given by,
𝑙 2
2∫0 [𝑓(𝑥)]2 𝑑𝑥 = 𝑙[∑∞
𝑛=1 𝑏𝑛 ]
𝜋 ∞
2
𝟐
⟹ 2 ∫ (1) 𝑑𝑥 = 𝜋 [∑( [𝟏 − (−𝟏)𝒏 ])2 ]
0 𝒏𝝅
𝑛=1
4 4 4
⟹ 2[𝑥]𝜋0 = 𝜋2 [4 + 32 + 52 + ⋯ … … … … … … . . ]
1 1 1 𝜋2
⟹ 12 + 32 + 52 + ⋯ ……………..= 8
REFERENCES:
1. Higher Engineering Mathematics-B.S. Grewal
2. Higher Engineering Mathematics-B.V. Ramana
*************************************************************
NOTES: CLASS-6
Parseval’s Identity:
𝑙 ∞
𝑎0 2
∫ [𝑓(𝑥)]2 𝑑𝑥 = 𝑙 [ + ∑(𝑎𝑛 2 + 𝑏𝑛 2 )]
−𝑙 2
𝑛=1
Problem 1. Find the Fourier Series expansion of period 2𝜋 for the function
𝑥(𝜋 − 𝑥), − 𝜋 ≤ 𝑥 ≤ 0
𝑓(𝑥) = {
𝑥(𝜋 + 𝑥), −𝜋 ≤ 𝑥 ≤ 0
Solution : Since 𝑓(𝑥) = −𝑥(𝜋 + 𝑥)𝑖𝑛 (−𝜋, 0) = −𝑓(𝑥)𝑖𝑛 (0, 𝜋)
and 𝑓(−𝑥) = 𝑥(𝜋 − 𝑥)𝑖𝑛 (0, 𝜋) = −𝑓(𝑥)𝑖𝑛 (−𝜋, 0), 𝑓(𝑥)is an odd function.
Then the Fourier Series expansion of 𝑓(𝑥) is given by,
𝑓(𝑥) = ∑∞
𝑛=1 𝑏𝑛 𝑠𝑖𝑛𝑛𝑥
where
1 𝜋
𝑏𝑛 = 𝜋 ∫−𝜋 𝑓(𝑥)𝑠𝑖𝑛𝑛𝑥𝑑𝑥
1 0 𝜋
= 𝜋 {∫−𝜋 𝑥(𝜋 − 𝑥)𝑠𝑖𝑛𝑛𝑥𝑑𝑥 + ∫0 𝑥(𝜋 + 𝑥)𝑠𝑖𝑛𝑛𝑥𝑑𝑥 }
0 𝜋
1 ∫−𝜋(𝜋𝑥𝑠𝑖𝑛𝑛𝑥 − 𝜋𝑥 2 𝑠𝑖𝑛𝑛𝑥)𝑑𝑥 + ∫0 (𝜋𝑥𝑠𝑖𝑛𝑛𝑥 + 𝜋𝑥 2 𝑠𝑖𝑛𝑛𝑥)𝑑𝑥
= 𝜋{ }
0 𝜋
1 ∫−𝜋(𝜋𝑥𝑠𝑖𝑛𝑛𝑥 − 𝑥 2 𝑠𝑖𝑛𝑛𝑥)𝑑𝑥 + ∫0 (𝜋𝑥𝑠𝑖𝑛𝑛𝑥 + 𝑥 2 𝑠𝑖𝑛𝑛𝑥)𝑑𝑥
= 𝜋{ }
1 4 4𝜋 2 (−1)𝑛 4(−1)𝑛
= 𝜋 {− 𝑛3 − + }
𝑛 𝑛3
4 (−1)𝑛 − 1 𝜋 2 (−1)𝑛
⟹ 𝑏𝑛 = { − }
𝜋 𝑛3 𝑛
Therefore, 𝑓(𝑥) = ∑∞
𝑛=1 𝑏𝑛 𝑠𝑖𝑛𝑛𝑥
4 (−1)𝑛 −1 𝜋 2 (−1)𝑛
⟹ 𝑓(𝑥) = ∑∞
𝑛=1 { − } 𝑠𝑖𝑛𝑛𝑥
𝜋 𝑛3 𝑛
Problem 2: Obtain the Fourier Series to represent the function 𝑓(𝑥) = |𝑥|, − 𝜋 < 𝑥 < 𝜋.
Solution : Since 𝑓(−𝑥) = |−𝑥| = |𝑥| = 𝑓(𝑥) , 𝑓(𝑥) is an even function.
𝑎0
The Fourier Series expansion of 𝑓(𝑥) is 𝑓(𝑥) = + ∑∞
𝑛=1 𝑎𝑛 𝑐𝑜𝑠𝑛𝑥
2
where
2 𝜋
𝑎0 = 𝜋 ∫0 𝑥𝑑𝑥
𝜋
2 𝑥2
= 𝜋[2]
0
⟹ 𝑎0 = 𝜋
𝜋
2
𝑎𝑛 = ∫ 𝑥𝑐𝑜𝑠𝑛𝑥𝑑𝑥
𝜋
0
2 (𝑠𝑖𝑛𝑛𝑥) (−𝑐𝑜𝑠𝑛𝑥) 𝜋
= 𝜋 [𝑥. − (1). ]
𝑛 𝑛2 0
2
⟹ 𝑎𝑛 = [(−1)𝑛 − 1]
𝜋𝑛2
𝜋 2
⟹ 𝑓(𝑥) = 2 + ∑∞ 𝑛
𝑛=1 𝜋𝑛2 [(−1) − 1]𝑐𝑜𝑠𝑛𝑥
-------------------------------------------------------------------------------------------------------------------
Problem 3. Obtain the Fourier Series for the function 𝑓(𝑥) = 𝑥 2 , − 𝜋 < x < 𝜋. Hence show that
𝟏 𝝅𝟒
∑ = 𝟗𝟎
𝒏𝟒
where
2 𝜋 2
𝑎0 = ∫ 𝑥 𝑑𝑥,
𝜋 0
𝜋
2 𝑥3
= 𝜋[3]
0
2𝜋 2
⟹ 𝑎0 = 3
2 𝜋
𝑎𝑛 = ∫ 𝑓(𝑥) 𝑐𝑜𝑠𝑛𝑥 𝑑𝑥
𝜋 0
2 𝜋
= ∫0 (𝑥 2 )𝑐𝑜𝑠𝑛𝑥 𝑑𝑥
𝜋
2 sin 𝑛𝑥 cos 𝑛𝑥 sin 𝑛𝑥 𝜋
=𝜋 [(𝑥 2 ) ( ) − (2𝑥) (− ) + 2 (− )]
𝑛 𝑛2 𝑛3 0
2 cos 𝑛𝑥 𝜋
= 𝜋 [(2𝑥) ( )]
𝑛2 0
2
= [(2𝜋) (cos 𝑛𝜋 − 0]
𝜋𝑛2
1
= cos 𝑛𝜋(4𝜋)
𝜋𝑛2
4
⟹ 𝑎𝑛 = (−1)𝑛
𝑛2
The required Fourier series is given by
∞
𝑎0
𝑓(𝑥) = + ∑(𝑎𝑛 𝑐𝑜𝑠 𝑛𝑥)
2
𝑛=1
2𝜋 2 1 4
⟹ 𝑥2 = ( ) 2 + ∑∞ 𝑛
𝑛=1 {𝑛2 (−1) 𝑐𝑜𝑠 𝑛𝑥}
3
𝜋2 4
⟹ 𝑥2 = + ∑∞ 𝑛
𝑛=1 {𝑛2 (−1) 𝑐𝑜𝑠 𝑛𝑥}
3
Deduction :
Consider the Parseval’s identity given by
𝜋 2 ∞ 2
2 ]2
1 2𝜋 2 4
⟹ ∫[𝑥 𝑑𝑥 = 𝜋 { ( ) + ∑ ([ 2 (−1)𝑛 𝑐𝑜𝑠 𝑛𝑥] + 0)}
2 3 𝑛
−𝜋 𝑛=1
𝜋 ∞
4
2𝜋 2 16
⟹ ∫ 𝑥 𝑑𝑥 = 𝜋 { + ∑ 4}
9 𝑛
−𝜋 𝑛=1
5 𝜋 ∞
𝑥 2𝜋 2 1
⟹ [ ] = 𝜋{ + 16 ∑ 4 }
5 −𝜋 9 𝑛
𝑛=1
∞
2𝜋 5 2𝜋 2 1
⟹ = 𝜋{ + 16 ∑ 4 }
5 9 𝑛
𝑛=1
∞
2𝜋 4 2𝜋 2 1
⟹ = + 16 ∑ 4
5 9 𝑛
𝑛=1
∞
2𝜋 4 2𝜋 2 1
⟹ − = 16 ∑ 4
5 9 𝑛
𝑛=1
∞
𝜋4 1
⟹∑ 4=
𝑛 90
𝑛=1
REFERENCES:
1. Higher Engineering Mathematics-B.S. Grewal
2. Higher Engineering Mathematics-B.V. Ramana
*************************************************************
NOTES: CLASS-7
Harmonic Analysis
It is the process of finding the constant term and the first few cosine and sine terms numerically.
Data:
x 𝑥1 𝑥2 𝑥3 ……. 𝑥𝑁
y 𝑦1 𝑦2 𝑦3 ……. 𝑦𝑁
2𝞹 2 2 2
𝑎0 = ∑𝑦 𝑎𝑛 = 𝑁 ∑ 𝑦cosnx 𝑏𝑛 = 𝑁 ∑ 𝑦 sinnx
𝑁
2l 2 𝑎𝑛 = 2 𝑛𝜋𝑥
𝑎0 = ∑𝑦 𝑏𝑛 = ∑ 𝑦 sin ( )
𝑁 2 𝑛𝜋𝑥 𝑁 𝑙
∑ 𝑦cos( )
𝑁 𝑙
Solution :
Length of interval = 2𝜋
No. of intervals, N = 6
2 2 1
𝑎0 = 𝑁 ∑ 𝑦 = ∑ 𝑦= (26.9) = 8.9667
6 3
2 2
𝑎𝑛 = ∑ 𝑦 cos𝑛𝑥 𝑏𝑛 = ∑ 𝑦 𝑠𝑖𝑛𝑛𝑥
𝑁 𝑁
2 2
𝑎1 = 6 ∑ 𝑦𝑐𝑜𝑠𝑥 𝑏1 = ∑ 𝑦 𝑠𝑖𝑛𝑥
6
1 1
= 3 ∑ 𝑦𝑐𝑜𝑠𝑥 = 3 ∑ 𝑦𝑠𝑖𝑛𝑥
0 7.9 1 7.9 0 0
𝜋⁄ 7.2 0.5 3.6 0.87 6.2352
3
2𝜋⁄ 3.6 -0.5 -1.8 0.87 3.1176
3
𝜋 0.5 -1 -0.5 0 0
4𝜋⁄ 0.9 -0.5 -0.45 -0.87 -0.7794
3
5𝜋⁄ 6.8 0.5 3.4 -0.87 -5.8888
3
Total ∑ 𝑦 =26.9 ∑ 𝑦𝑐𝑜𝑠𝑥 =12.15 ∑ 𝑦𝑠𝑖𝑛𝑥 =2.6846
2 2 1
𝑎0 = 𝑁 ∑ 𝑦 = ∑ 𝑦= (26.9) = 8.9667
6 3
1 1
𝑎1 = 𝟑 ∑ 𝑦𝑐𝑜𝑠𝑥 = 𝟑 [𝟏𝟐. 𝟏𝟓] = 4.05
1 1
𝑏1 = 𝟑 ∑ 𝑦𝑠𝑖𝑛𝑥 = 𝟑 [𝟐. 𝟔𝟖𝟒𝟔] = 0.8949
REFERENCES:
1. Higher Engineering Mathematics-B.S. Grewal
2. Higher Engineering Mathematics-B.V. Ramana
*************************************************************
NOTES: CLASS-8
Harmonic Analysis
Problem 2. Determine the first 3 coefficients of cosine and two coefficient of sine terms in the
Fourier series for the following data
X 0 𝜋⁄ 𝜋⁄ 𝜋⁄ 2𝜋⁄ 5𝜋⁄
6 3 2 3 6
Y 0 9.2 14.4 17.8 17.3 11.7
Solution :
𝜋
Length of interval is 2𝑙 = 𝜋⟹ 𝑙 = 2
2 𝑛𝜋𝑥 2 𝑛𝜋𝑥
𝑎𝑛 = ∑ 𝑦 cos ( ) 𝑏𝑛 = ∑ 𝑦 𝑠𝑖𝑛 ( )
𝑁 𝑙 𝑁 𝑙
2 𝑛𝜋𝑥 2 𝑛𝜋𝑥
= 6 ∑ 𝑦 cos ( 𝜋 ) = 6 ∑ 𝑦 cos ( 𝜋 )
⁄2 ⁄2
1 1
= 3 ∑ 𝑦 cos (2𝑛𝑥) = 3 ∑ 𝑦𝑠𝑖𝑛(2𝑛𝑥)
Cosine Terms
1
𝑎𝑛 = 𝟑 ∑ 𝑦 cos2nx
1 1
𝑎1 = 𝟑 ∑ 𝑦 cos2x = 𝟑 [−𝟐𝟑. 𝟐] = −7.73
1 1
𝑎2 = 𝟑 ∑ 𝑦 cos4x = 𝟑 [−𝟖. 𝟓] = −2.83
-4.698
1
𝑏𝑛 = 𝟑 ∑ 𝑦𝑠𝑖𝑛𝑛𝑥
1 1
𝑏1 = 𝟑 ∑ 𝑦𝑠𝑖𝑛2𝑥 = 𝟑 [−4.698] = −7.73
1 1
𝑏2 = 𝟑 ∑ 𝑦𝑠𝑖𝑛4𝑥 = 𝟑 [0.348] = 0.116
REFERENCES:
1. Higher Engineering Mathematics-B.S. Grewal
2. Higher Engineering Mathematics-B.V. Ramana
*************************************************************
NOTES: CLASS-9
Complex form of Fourier series
The complex exponential form of the Fourier series is
𝒊𝒏𝝅𝒙 𝒄+𝟐𝑳 −𝒊𝒏𝝅𝒙
𝟏
𝒇(𝒙) = ∑∞
𝒏=−∞ 𝒄𝒏 𝒆 𝒍 where 𝒄𝒏 = 𝟐𝑳 ∫𝒄 𝒇(𝒙)𝒆 𝑳 𝒅𝒙.
𝑓(𝑥) = ∑ 𝑐𝑛 𝑒 𝑖𝑛𝜋𝑥/𝑙
𝑛=−∞
where
1 𝑙
𝑐𝑛 = 2𝑙 ∫−𝑙 𝑓(𝑥)𝑒 −𝑖𝑛𝜋𝑥/𝑙 𝑑𝑥 .
1 1
= 2 ∫−1 𝑒 −𝑥 𝑒 −𝑖𝑛𝜋𝑥/1 𝑑𝑥
1 1
= 2 ∫−1 𝑒 −(𝑖𝑛𝜋+1)𝑥 𝑑𝑥
1
1 𝑒 −(𝑖𝑛𝜋+1)𝑥
= 2 [ −(𝑖𝑛𝜋+1) ]
−1
𝑒 −(𝑖𝑛𝜋+1) −𝑒 (𝑖𝑛𝜋+1)
= −2(𝑖𝑛𝜋+1)
𝑒 (𝑖𝑛𝜋+1) −𝑒 −(𝑖𝑛𝜋+1)
= 2(𝑖𝑛𝜋+1)
𝑒 1 .𝑒 𝑖𝑛𝜋 −𝑒 −1 .𝑒 −𝑖𝑛𝜋+1
= 2(𝑖𝑛𝜋+1)
𝑒(𝑐𝑜𝑠𝑛𝜋+𝑖𝑠𝑖𝑛𝑛𝜋)−𝑒 −1 (𝑐𝑜𝑠𝑛𝜋+𝑖𝑠𝑖𝑛𝑛𝜋)
= 2(𝑖𝑛𝜋+1)
𝑒.𝑐𝑜𝑠𝑛𝜋−𝑒 −1 .𝑐𝑜𝑠𝑛𝜋
= 2(𝑖𝑛𝜋+1)
(𝑒.−𝑒 −1 )(−1)𝑛
= 2(𝑖𝑛𝜋+1)
(−1)𝑛 𝑠𝑖𝑛ℎ1
= (𝑖𝑛𝜋+1)
(−1)𝑛 𝑠𝑖𝑛ℎ1
= (𝑖𝑛𝜋+1)
(−1)𝑛 𝑠𝑖𝑛ℎ1(−𝑖𝑛𝜋+1)
= (𝑖𝑛𝜋+1)(−𝑖𝑛𝜋+1)
(−1)𝑛 𝑠𝑖𝑛ℎ1(−𝑖𝑛𝜋 + 1)
⟹ 𝑐𝑛 =
(𝑛2 𝜋 2 + 1)
∞
−𝑥
(−1)𝑛 𝑠𝑖𝑛ℎ1(−𝑖𝑛𝜋 + 1) 𝑖𝑛𝜋𝑥
⟹𝑒 = ∑ 𝑒
(𝑛2 𝜋 2 + 1)
𝑛=−∞
REFERENCES:
1. Higher Engineering Mathematics-B.S. Grewal
2. Higher Engineering Mathematics-B.V. Ramana
*************************************************************
NOTES: CLASS-10
Complex form of Fourier series
Problem 2. Find the complex form of the Fourier Series of 𝑓(𝑥) = 𝑐𝑜𝑠𝑎𝑥 − 𝜋 ≤ 𝑥 ≤ 𝜋.
Solution : Here period, 2𝑙 = 2𝜋 ⟹ 𝑙 = 𝜋
𝑓(𝑥) = ∑ 𝑐𝑛 𝑒 𝑖𝑛𝜋𝑥/𝑙
𝑛=−∞
where
𝑙
1
𝑐𝑛 = ∫ 𝑓(𝑥)𝑒 −𝑖𝑛𝜋𝑥/𝑙 𝑑𝑥
2𝑙
−𝑙
1 𝜋
= 2𝜋 ∫−𝜋 𝑒 −𝑖𝑛𝜋𝑥 𝑐𝑜𝑠𝑎𝑥𝑑𝑥.
𝜋
1 𝑒 −𝑖𝑛𝑥
= 2𝜋 {𝑎2 +𝑖 2 𝑛2 [−𝑖𝑛𝑐𝑜𝑠𝑎𝑥 + 𝑎𝑠𝑖𝑛𝑎𝑥]}
−𝜋
𝑒 𝑎𝑥
{𝑆𝑖𝑛𝑐𝑒, ∫ 𝑒 𝑎𝑥 𝑐𝑜𝑠𝑏𝑥𝑑𝑥 = 𝑎2 +𝑏2 [𝑎𝑐𝑜𝑠𝑏𝑥 + 𝑏𝑠𝑖𝑛𝑏𝑥]}
1 𝑒 −𝑖𝑛𝜋 𝑒 𝑖𝑛𝜋
= { 2 [−𝑖𝑛𝑐𝑜𝑠𝑎𝜋 + 𝑎𝑠𝑖𝑛𝑎𝜋] − [−𝑖𝑛𝑐𝑜𝑠𝑎𝜋 − 𝑎𝑠𝑖𝑛𝑎𝜋]}
2𝜋 𝑎 − 𝑛2 𝑎 2 − 𝑛2
(−𝑒 −𝑖𝑛𝜋 +𝑒 −𝑖𝑛𝜋 ) (𝑒 −𝑖𝑛𝜋 +𝑒 −𝑖𝑛𝜋 )
= . 𝑖𝑛𝑐𝑜𝑠𝑎𝜋 + . 𝑎 𝑠𝑖𝑛𝑎𝜋
2𝜋(𝑎2 −𝑛2 ) 2𝜋(𝑎2 −𝑛2 )
sin 𝑛𝜋 𝑐𝑜𝑠𝑛𝜋
= 𝜋(𝑎2 −𝑛2 ) . 𝑖𝑛𝑐𝑜𝑠𝑎𝜋 + 𝜋(𝑎2 −𝑛2 ) . 𝑎𝑠𝑖𝑛𝑎𝜋
(−1)𝑛
⟹ 𝑐𝑛 = . 𝑎𝑠𝑖𝑛𝑎𝜋
𝜋(𝑎2 − 𝑛2 )
∞
(−1)𝑛 𝑎𝑠𝑖𝑛𝑎𝜋 𝑖𝑛𝑥
⟹ 𝑐𝑜𝑠𝑎𝑥 = ∑ .𝑒
𝜋(𝑎2 − 𝑛2 )
𝑛=−∞
REFERENCES:
1. Higher Engineering Mathematics-B.S. Grewal
2. Higher Engineering Mathematics-B.V. Ramana
*************************************************************